Analysis of patients' knowledge on risk factors of cardiovascular diseases and new technology of self-control this factors - especially with cholesterol - Anna Staniszewska; Dominik Olejniczak; Elwira Smoleńska; Aleksandra Kielan (Kazimierz Wielki University, 2017)
Many determinants of cardiovascular risk have been identified. Lack of knowledge about common risk factors of cardiovascular diseases could provoke their underestimation  and confer further risk increase. New medical technology helps patient's by self-care.